2022
DOI: 10.3389/fbioe.2022.966062
|View full text |Cite
|
Sign up to set email alerts
|

Lysine acetylation of Escherichia coli lactate dehydrogenase regulates enzyme activity and lactate synthesis

Abstract: As an evolutionarily conserved posttranslational modification, protein lysine acetylation plays important roles in many physiological and metabolic processes. However, there are few reports about the applications of lysine acetylation in metabolic regulations. Lactate is a main byproduct in microbial fermentation, and itself also an important bulk chemical with considerable commercial values in many fields. Lactate dehydrogenase (LdhA) is the key enzyme catalyzing lactate synthesis from pyruvate. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…functionality [60]. Also, it has been approved that: Lysine acetylation in Escherichia coli regulates enzyme activity and lactate synthesis [61]. The lysine acylation necessary for activating E coli, and allows the actual effects of lysine acetylation for protein productive functions [62].…”
Section: Figurementioning
confidence: 99%
“…functionality [60]. Also, it has been approved that: Lysine acetylation in Escherichia coli regulates enzyme activity and lactate synthesis [61]. The lysine acylation necessary for activating E coli, and allows the actual effects of lysine acetylation for protein productive functions [62].…”
Section: Figurementioning
confidence: 99%
“…However, residue K9 also showed the same decrease in the acetylation levels, but its enzymatic activity increased 2.5-fold. According to the 3D-modelled structure of LdhA, K154 may be involved in binding the substrate and cofactor, while K248 and K9 are not the catalytic key sites, but both help stabilize the LdhA conformation ( Liu et al., 2022 ).…”
Section: Cellular Processes Regulated By Acetylationmentioning
confidence: 99%
“…To further confirm the significance of Lys182 on the impact of TTF-1 on target gene expression, we introduced another mutation in TTF-1, substituting Lys182 with arginine (K182R). Previous studies indicated that Lys-to-arginine mutants maintain a positive charge and are incapable of being acetylated, effectively mimicking a deacetylated state of Lys [38,39]. In accordance with this, the K182R mutant of TTF-1 enhanced AgRP promoter activity (Figure 6A) and AgRP mRNA expression (Figure 6C) and diminished POMC promoter activity (Figure 6B) and POMC mRNA expression (Figure 6D), which are opposite effects to those of the K182Q mutant of TTF-1, which mimics acetylated TTF-1.…”
Section: Impact Of Lys182 Mutation On Ttf-1 Activities In Regulating ...mentioning
confidence: 99%